Highly photocatalytic TiO2 interconnected porous powder fabricated by sponge-templated atomic layer deposition. (17th August 2015) - Pan, Shengqiang; Zhao, Yuting; Huang, Gaoshan; Wang, Jiao; Baunack, Stefan; Gemming, Thomas; Li, Menglin; Zheng, Lirong; Schmidt, Oliver G; Mei, Yongfeng
Abstract: A titanium dioxide (TiO2 ) interconnected porous structure has been fabricated by means of atomic layer deposition of TiO2 onto a reticular sponge template. The obtained freestanding TiO2 with large surface area can be easily taken out of the water to solve a complex separation procedure. A compact and conformal nanocoating was evidenced by morphologic characterization. A phase transition, as well as production of oxygen vacancies with increasing annealing temperature, was detected by x-ray diffraction and x-ray photoelectron spectroscopy, respectively. The photocatalytic experimental results demonstrated that the powder with appropriate annealing treatment possessed excellent photocatalytic ability due to the co-action of high surface area, oxygen vacancies and the optimal crystal structure.